“Now You Can Return Home”: a Narrativized Account of an Insurgency and Pursuit of Peace and Solidarity - Pokharel, Badri Prasad (KMC Research Journal, 2024)
This paper analyzes the painful plight and longing for peace and solidarity among the war affected people during the decade long Maoist insurgency which escalated the conflict for a long time confiscating the lives of thousands of people from both fighting groups and other sandwiched innocent denizens. During this insurgency, the state’s functional bodies were not working, common people were on the dilemma of either living or leaving their places and were longing for a lasting peace and solidary so that they could return home and live once again in the same way. In this paper, I have analyzed some fundamental questions based on the different grounds from Madhuban Paudel’s story “Now You can Return Home”: Why are the people like Sarad and Mukunda victimized during the conflict? Why is peace important factor for the sustainable development of the country? How would peace and solidarity be prevailed in the war affected society? I have discussed these questions in this article with the reference with historical background of Nepal’s sociopolitical scenario, peace and trauma theory.